Determinan Kurangnya Aktivitas Olahraga pada Remaja Menurut Teori Health Belief Model : Tinjauan Pustaka Tahun 2010-2025 - Rifki Luthfiyan Ramadhan; Luqman Effendi (Pusat Riset dan Inovasi Nasional, 2026)
Lack of physical activity among adolescents is a significant public health problem in Indonesia and globally, contributing to increased risks of obesity, metabolic disorders, declining quality of life, and other health issues. This condition is influenced by various internal determinants, particularly psychological factors such as perceived barriers, lack of motivation, and low self-efficacy. This study aims to identify the determinants of lack of physical activity among adolescents based on the Health Belief Model (HBM) theory. This research used a literature review design. Data were obtained by collecting, analyzing, and organizing articles and previous studies discussing determinants of physical inactivity among adolescents using HBM. Perceptions directly related to the determinants of physical inactivity identified in this review were perceived barriers, perceived vulnerability, and self-efficacy. Several other HBM components, such as perceived benefits and cues to action, were found to be less consistently associated with physical activity behavior in adolescents. Lack of physical activity and health risks are closely related to internal factors, especially perceptions and self-efficacy. Adolescents who are not aware of the health risks and benefits of exercise tend to ignore physical activity, whereas awareness of risks and strong self-efficacy encourage more active behavior.